PERTANGUNGG JAWABAN HUKUM TERHADAP KORBAN ANAK DALAM KEKERASAN SEKSUAL TERHADAP ANAK DIKAITKAN DENGAN HUKUM PERLINDUNGAN ANAK UU NO 35 TAHUN 2014 TENTANG PERUBAHAN ATAS UU NO 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Angelina, Putu Dian; Yudiantara, I Gusti Ngurah Nyoman Krisnadi (Kertha Semaya : Journal Ilmu Hukum; Vol 12 No 10 (2024)DO - 10.24843/KS.2024.v12.i10.p11, 2024)
Tujuan penulis jurnal ini adalah untuk menelaah pengaturan dan pertangungg jawaban pidana bagi pelaku kekerasan seksual yang menyebabkan anak menjadi terganggu untuk meraih masa depan. Kekerasan pada anak s eringkali, masyarakat, terutama orang tua dan keluarga dengan anak kecil, merasa khawatir karena pelecehan seksual masih menjadi masalah yang kerap muncul saat ini. Dengan demikian, peranan orang tua dan keluarga sangat penting dalam mendeteksi tanda-tanda pelecehan atau kekerasan seksual pada anak. Dampak kekerasan seksual ini sangat luas, termasuk dampak kesehatan dan terutama dampak psikologis yang dapat berlanjut hingga dewasa. Anak dapat mengalami trauma, kehilangan kepercayaan pada orang dewasa, merasa tidak aman, dan merasa tidak berdaya. Meskipun dampak fisik mungkin tidak terlalu terlihat, dampak psikologisnya dapat sangat merusak. Oleh karena itu, peranan orang tua, keluarga, dan masyarakat dalam melindungi anak sangat penting, termasuk melalui sistem kesejahteraan sosial dan komunikasi yang terbuka agar anak dapat dibekali dan dilindungi dari potensi kejahatan tersebut serta membangun hubungan yang positif.    ABSTRACT The aim of the authors of this journal is to examine criminal arrangements and accountability for perpetrators of sexual violence that cause children to be disturbed from achieving a future. Violence against children often makes people concerned, especially parents and families who have small children to be more vigilant. Sexual harassment is still a phenomenon that still occurs frequently these days. This is the role of parents, the family is very important to explore signs of children experiencing sexual harassment or violence. The impact experienced by children who received sexual violence is very long-lasting, besides having an impact on their health, another impact that is very influential is the impact on their mentality which will experience prolonged trauma or even until they are adults. Children will experience trauma as a result of sexual violence such as losing the child’s trust in adults, feeling insecure, sexually traumatized, and feeling helpless. Physically it may not bee to influential but mentally or psychologically it causes trauma and mental disorders that are not good. Here the role of parents, family, society is very important in providing protection for children, it is necessary to have a system, which includes a social welfare system for children and families. Communication is one of the solutions in preventing sexual violence that occurs in children, in addition to establishing communication so that a family can be open and harmonious with each other. Parents and families can provide protection to children through communication that exists between the two so that they can equip and protect children from lurking evil, create an attitude of openness, mutual respect, mutual respect and attitudes that support positive things done to children.